Analisis Perubahan Penggunaan Lahan Pertanian Tanaman Mendong di Desa Blayu, Kecamatan Wajak - Ramadhani, Nur; Kusufa, Roni Alim Ba'diya; Putra, Dwi Fauzia (PT. Pubsains Nur Cendekia, 2024)
The mendong plant is one of the plants that is widely cultivated by people in Blayu Village, Wajak District. However, the number of farmers cultivating mendong plants is decreasing, so the agricultural land for mendong plants is starting to decrease. This research aims to: 1) analyze changes in land use for mendong crop farming in Blayu Village; and 2) know the factors that cause changes in agricultural land use for mendong crops. This research uses a descriptive survey method by collecting several samples in the form of people through questions. Google Earth was used to analyze changes in the use of agricultural land for mendong crops in Blayu Village from 2010 to 2024. Based on the results of the analysis of changes in agricultural land use for mendong crops in Blayu Village in 2010-2024, an increase in changes in the area of ​​mendong crops was obtained by 26.45 ha or 91.4 %. Meanwhile, the factors causing changes in the use of agricultural land for mendong plants in Blayu Village are economic factors, labor, mendong craftsmen, and the availability of mendong plant drying equipment.